(untitled) (Research, Society and Development, 2020)
This article deals with the teaching of accessible tourism based on the analysis of legislation regarding people with disabilities, supported by the Problem Based Learning (PBL) methodology and adapted to the precepts of action research. The article aims to identify the needs and the level of knowledge of students, investigated in the classes of Legislation Applied to Tourism, of the third year of the technical level course integrated into the tour guide from IFAL’s Marechal Deodoro campus. The educational product of an accessible tourism study guide was developed, designed to enrich the student’s professional training. We opted for qualitative and quantitative research, of an exploratory nature, with the use of documentary research for bibliographic review and questionnaires, for data collection, applied to students. The exposed results indicated that the majority of students did not know the subject, but they have an interest in studying, therefore, there is space and relevance for the application of the educational product that will contribute for the adequate training of future professionals and citizens sensitive to the challenge of implementing accessibility for all.